Impaired regulation of emotion: neural correlates of reappraisal and distraction in bipolar disorder and unaffected relatives - Kanske, Philipp; Forneck, Johanna (Translational Psychiatry, 2015)
Deficient emotion regulation has been proposed as a crucial pathological mechanism in bipolar disorder (BD). We therefore investigated emotion regulation impairments in BD, the related neural underpinnings and their etiological relevance for the disorder. Twenty-two euthymic patients with bipolar-I disorder and 17 unaffected first-degree relatives of BD-I patients, as well as two groups of healthy gender-, age- and education-matched controls (N=22/17, respectively) were included. Participants underwent functional magnetic resonance imaging while applying two different emotion regulation techniques, reappraisal and distraction, when presented with emotional images. BD patients and relatives showed impaired downregulation of amygdala activity during reappraisal, but not during distraction, when compared with controls. This deficit was correlated with the habitual use of reappraisal. The negative connectivity of amygdala and orbitofrontal cortex (OFC) observed during reappraisal in controls was reversed in BD patients and relatives. There were no significant differences between BD patients and relatives. As being observed in BD patients and unaffected relatives, deficits in emotion regulation through reappraisal may represent heritable neurobiological abnormalities underlying BD. The neural mechanisms include impaired control of amygdala reactivity to emotional stimuli and dysfunctional connectivity of the amygdala to regulatory control regions in the OFC. These are, thus, important aspects of the neurobiological basis of increased vulnerability for BD.
Gesehen am 12.06.2020